Learning about oneself: The effects of performance feedback on school choice - Matteo Bobba; Verónica Frisancho Robles (Inter-American Development Bank (IDB), 2016)
This paper designs and implements a field experiment that provides students from less advantaged backgrounds with individualized feedback on academic performance during the transition from middle to high school. The intervention reduces the gap between expected and actual performance, as well as shrinks the variance of individual ability distributions. Guided by a simple Bayesian model, the paper empirically documents the interplay between variance reductions and mean changes of beliefs in shaping curricular choices. The shift in revealed preferences on high school tracks enabled by the intervention affects schooling trajectories, with better-performing students being assigned into more academically oriented options.
Keywords: D83; I21; I24; J24; 330; Information; Bayesian updating; Biased beliefs; School choice